2014
DOI: 10.1177/1077801214559057
|View full text |Cite
|
Sign up to set email alerts
|

Jordanian Nurses’ Barriers to Screening for Intimate Partner Violence

Abstract: Screening rates for intimate partner violence (IPV) among nurses are still very low. The study purpose is to evaluate IPV screening and barriers by Jordanian nurses. A cross-sectional design was used with a stratified random sample (N = 125) of Jordanian nurses. Findings included a significantly lower IPV screening rate among Jordanian nurses compared with those in the United States, no difference in screening between IPV victims compared with non-victimized nurses, and that the IPV screening barriers related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
40
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 71 publications
10
40
0
2
Order By: Relevance
“…Moreover, the allocated resources to this field are not sufficient, due to which few nurses may feel desperate, leading them to be reluctant professionally. Nevertheless, nurses often owns a commitment and opportunity to manage and identify the DVA/IPV (Al‐Natour et al., ; Glaister & Kesling, ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the allocated resources to this field are not sufficient, due to which few nurses may feel desperate, leading them to be reluctant professionally. Nevertheless, nurses often owns a commitment and opportunity to manage and identify the DVA/IPV (Al‐Natour et al., ; Glaister & Kesling, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, research in Jordan has found that most partner violence survivors do not seek help in the health sector;11 and when identified in the health sector, patients are generally dissatisfied with the health provider response 49. Screening rates among Jordanian nurses are low and significant barriers to effective screening have been documented, especially a lack of institutional supports 50. Survivor blaming and tolerance of abuse to discipline an errant wife are also pervasive,11 50 and undermine the effectiveness of screening.…”
Section: Discussionmentioning
confidence: 99%
“…Screening rates among Jordanian nurses are low and significant barriers to effective screening have been documented, especially a lack of institutional supports 50. Survivor blaming and tolerance of abuse to discipline an errant wife are also pervasive,11 50 and undermine the effectiveness of screening. Given the social repercussions of help-seeking and divorce, and widespread tolerance of abuse, building a stronger healthcare response will not only require improving screening practices, but will also require addressing the stigma associated with help-seeking outside the family and they myriad contributors to women's disempowerment.…”
Section: Discussionmentioning
confidence: 99%
“…However, even where nurses have the skills to identify DVA (Sundborg et al, 2012) medical care is often prioritised in order to avoid screening despite suspicions (Al Natour, 2014).…”
Section: Screening Inquiry and The Therapeutic Relationshipmentioning
confidence: 99%